A study on quantifying carbon content in two species mixed mangroves planted in Nam Phu commune, Tien Hai district, Thai Binh province - Hong Hanh, Nguyen Thi (Academia Journal of Biology, 2015)
In order to evaluate the effect of carbon accumulation of two species mixed mangroves contributing to reduction of greenhouse gas emission, adaptatiing to climate change, and providing scientific basis for international negotiations in REDD, REDD+ programmes, our study was carried out from June 2013 to December 2014. The study was focusing on the carbon accumulation in two mixed species mangroves of Kandelia obovata and Sonneratia caseolaris in ages 13, 11 and 10 years planted in Nam Phu commune, Tien Hai district, Thai Binh province. The results showed that the two species mixed mangroves with Kandelia obovata and Sonneratia caseolaris in ages 13, 11 and 10 years had accumulated 42.28 tC/ha (corresponding to 155.17 tons of CO2 was absorbed per hectare), 22.36 tC/ha (corresponding to 82.06 tons of CO2 was absorbed per hectare) and 17.04 tC/ha (corresponding to 62.53 tons of CO2 was absorbed per hectare), respectively. Carbon content accumulated in mangrove trees depends on species, age and tree density of the forests. Carbon content in biomass accumulated by Kandelia obovata mangrove is higher than that accumulated by Sonneratia caseolaris mangrove, this indicated that the mangrove with Kandelia obovata mangrove is better for carbon content accumulation for reducing greenhouse effects.